2016
DOI: 10.1590/0104-1428.2051
|View full text |Cite
|
Sign up to set email alerts
|

Influência do método de vulcanização nas propriedades mecânicas e na densidade de ligações cruzadas da borracha natural

Abstract: ResumoA vulcanização é um importante fator que determina as propriedades mecânicas da borracha, mas a influência do método de vulcanização nas propriedades mecânicas do material, ainda é um assunto pouco explorado na literatura. Neste artigo, uma formulação à base de poli-cis-isopreno ou borracha natural (NR), denominada NR4010-A, foi vulcanizada em prensa e autoclave, com o objetivo de avaliar a influência do método de vulcanização na formação das ligações cruzadas e, consequentemente, nas propriedades mecâni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 14 publications
3
7
0
7
Order By: Relevance
“…Oliveira et al . demonstrated that the density of polysulphidic links was reduced as the time of samples under pressure and temperature in a hydraulic press increased, corroborating with the results obtained in the present work.…”
Section: Mechanical Propertiessupporting
confidence: 93%
See 1 more Smart Citation
“…Oliveira et al . demonstrated that the density of polysulphidic links was reduced as the time of samples under pressure and temperature in a hydraulic press increased, corroborating with the results obtained in the present work.…”
Section: Mechanical Propertiessupporting
confidence: 93%
“…Crosslinking density is an important factor that affects the physical properties of the vulcanized elastomer . Related to this, the influence of density and crosslinking type in the mechanical properties of rubber has been studied by various authors, since the stress‐strain measurement is an indirect method for determining the crosslinking density …”
Section: Introductionmentioning
confidence: 99%
“…Tensile strength and elongation at break results of the samples are shown in Figure 2. The tensile strength results of the EPDM-r samples (Figure 2a) were in accordance with the values observed in Table 4 for MH, indicating that the increase of the cross-link density led to the observed increase of the tensile strength [36]. The tensile strength of the sample EPDM-r 30 was The tensile strength results of the EPDM-r samples (Figure 2a) were in accordance with the values observed in Table 4 for MH, indicating that the increase of the cross-link density led to the observed increase of the tensile strength [36].…”
Section: Mechanical Propertiessupporting
confidence: 86%
“…The tensile strength results of the EPDM-r samples (Figure 2a) were in accordance with the values observed in Table 4 for MH, indicating that the increase of the cross-link density led to the observed increase of the tensile strength [36]. The tensile strength of the sample EPDM-r 30 was The tensile strength results of the EPDM-r samples (Figure 2a) were in accordance with the values observed in Table 4 for MH, indicating that the increase of the cross-link density led to the observed increase of the tensile strength [36]. The tensile strength of the sample EPDM-r 30 was higher than that of the Control sample, indicating that 30 phr of EPDM-r can be added to the formulation without compromising the mechanical behavior of the composition.…”
Section: Mechanical Propertiessupporting
confidence: 86%
“…The elastomers subjected to the vulcanization process with sulfur exhibit physical, mechanical, and chemical changes due to the modification of its plastic state to the elastic state resulting from the formation of crosslinks between the polymer chains . In addition, the vulcanization kinetics may be altered by the use of accelerators, which are intended to improve the efficiency of crosslinks that occur during the vulcanization step .…”
Section: Introductionmentioning
confidence: 99%